Pengembangan Bahan Ajar Kontekstual Berbasis Hands On Activity dalam Pembelajaran Fisika pada Materi Gerak Melingkar - Arifuddin Arifuddin; Sutrio Sutrio; Muhammad Taufik (Kappa Journal, 2022)
This research is a development research that aims to produce products in the form of hands on activity based contextual teaching materials that are feasible and practical to use in learning. The research design is the development of a 4D model which consists of 4 stages, namely Define, Design, Develop and Disseminate. The product developed is contextual teaching materials based on hands on activity. Research data obtained from validation sheets and student response questionnaires. The results of data analysis determine the level of feasibility and practicality of the teaching materials developed. Feasibility of teaching materials in terms of the value of validity and reliability. The practicality of teaching materials in terms of the value of the results of student responses. The results showed the feasibility of teaching materials based on the validity value obtained a percentage of 87.18% with very valid criteria and the reliability value showed the acquisition of a percentage value of 94.521% with a reliable category. The results of the practicality of teaching materials based on the student's response value showed a percentage value of 91.42% with a good category. Thus, it can be concluded that the hands on activity based contextual teaching materials developed are feasible and practical to use in learning.